The Publishing Race - A.W. Misbach (The Thinker)
In October 2020, The Thinker received an open letter from Waghied Misbach as part of a call for papers on a special edition on “Race. Racism. Anti-Racism.” As this letter was about what he termed, “the erasure of black lives” in publishing, I decided to publish the letter and invited Terry Morris from Pan Macmillan to respond in the interests of fairness and open debate.